The Translation of Meitantei Conan Manga: The Comparison of Translator Ideology by Gender - Idrus, Idrus (NAWA: Journal of Japanese Studies, 2026)
This study examines the translation ideology applied by male and female translators in the Indonesian versions of the Meitantei Conan manga, with a focus on how Culture-Specific Items (CSIs) are rendered. Using a qualitative descriptive approach, the research analyzes linguistic units such as words, phrases, and clauses categorized under Axeila’s CSI framework. Newmark’s translation methods and Venuti’s concepts of foreignization and domestication serve as the theoretical basis for identifying ideological tendencies. Data were collected from the original manga and its Indonesian translations, supported by information from editors and translators involved in the publication process. Findings show that both male and female translators predominantly employ foreignization, indicating a shared preference for preserving Japanese cultural elements rather than fully adapting them to Indonesian norms. This tendency is evident across most CSI categories, including personal names, given names, brand names, foods, and measurements. However, gender-based differences appear in specific categories: male translators tend to domesticate folktales and myths, whereas female translators domesticate certain place names to enhance reader accessibility. Despite these differences, both groups demonstrate a consistent orientation toward maintaining cultural authenticity. Overall, the study concludes that translator gender influences specific stylistic choices but does not significantly alter the broader ideological pattern. The dominant use of foreignization reinforces the role of translated manga as a medium of cultural transmission, presenting Japanese cultural identity directly to Indonesian readers.